2016
DOI: 10.3390/ma9120993
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of a Borided Layer Formed on Ti-6Al-4V Alloy by Means of SMAT and Low-Temperature Boriding

Abstract: In this paper, a nanocrystalline surface layer without impurities was fabricated on Ti-6Al-4V alloy by means of surface mechanical attrition treatment (SMAT). The grain size in the nanocrystalline layer is about 10 nm and grain morphology displays a random crystallographic orientation distribution. Subsequently, the low-temperature boriding behaviors (at 600 °C) of the SMAT sample, including the phase composition, microstructure, micro-hardness, and brittleness, were investigated in comparison with those of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…www.advancedsciencenews.com www.aem-journal.com Figure 8 compares the XRD profiles of the MSB treated and untreated titanium plates after nitriding at various temperatures. As shown in Figure 8a and b, the surface layer contained strong diffraction peaks for the a-Ti(N), as well as weak diffraction peaks for TiN and Ti 2 N after nitriding at 600 C for 5 h. This result can be attributed to the XRD profiles providing phase information to a depth of 0-15 mm, [6] which is thicker than that of the nitrided layer (<1 mm). XRD profiles of the nitrided MSB plate exhibited higher intensities for TiN and Ti 2 N peaks than that of the nitrided coarse-grained plate.…”
Section: The Microstructures Of the Msb-treated Ti Plate For Various mentioning
confidence: 64%
See 1 more Smart Citation
“…www.advancedsciencenews.com www.aem-journal.com Figure 8 compares the XRD profiles of the MSB treated and untreated titanium plates after nitriding at various temperatures. As shown in Figure 8a and b, the surface layer contained strong diffraction peaks for the a-Ti(N), as well as weak diffraction peaks for TiN and Ti 2 N after nitriding at 600 C for 5 h. This result can be attributed to the XRD profiles providing phase information to a depth of 0-15 mm, [6] which is thicker than that of the nitrided layer (<1 mm). XRD profiles of the nitrided MSB plate exhibited higher intensities for TiN and Ti 2 N peaks than that of the nitrided coarse-grained plate.…”
Section: The Microstructures Of the Msb-treated Ti Plate For Various mentioning
confidence: 64%
“…[1][2][3][4] However, the low hardness values and poor wear resistance have seriously restricted its applications in some engineering fields. [5,6] It is well known that wear fatigue originates from the titanium surface, but the service life of the titanium plate can be improved by hardening the surface. [7,8] Nitriding is one of the most effective methods for improving surface hardness values and wear resistance for metal-based materials, [9][10][11] and these properties along with corrosion resistance can be significantly enhanced via nitriding treatments on titanium plates.…”
Section: Introductionmentioning
confidence: 99%
“…Surface nanocrystallization (SNC), which was proposed by Lu et al, is a surface SPD technology for processing gradient structured materials [ 16 , 17 ]. It has been reported that a gradient structure with nanograins on the surface can bring a better strength-ductility combination to many materials [ 18 , 19 , 20 , 21 ]. Wen et al [ 22 ] found that both the yield strength ( ) and ultimate tensile strength ( ) of gradient structured Ti increased by ~100 MPa after surface mechanical attrition treatment (SMAT) processing respectively, while retaining ~59% of the uniform elongation of the coarse-grained (CG) counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…Such a high nitriding temperature and long processing time result in high energy consumption, which increases the cost of production . In addition, the nitride layer formed during this process usually results in substantially lower surface toughness, which degrades the performance of titanium plate subjected to severe service environments involving high shear and compressive and/or impact loading conditions . Therefore, decreasing the nitriding temperature, while improving the toughness of the nitride layer is currently a major challenge for materials scientists.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that plasma nitriding could be carried out at 550 °C, which is significantly lower than conventional nitriding temperatures . Yao et al investigated the effect of a Ti–6Al–4V nanocrystalline layer produced by SMAT for enhancing the toughness of the borided layer . The results showed no obvious brittle cracking of the SMAT specimen after the boriding treatment.…”
Section: Introductionmentioning
confidence: 99%